2021
DOI: 10.1038/s41598-021-87403-8
|View full text |Cite
|
Sign up to set email alerts
|

Exhausting repetitive piano tasks lead to local forearm manifestation of muscle fatigue and negatively affect musical parameters

Abstract: Muscle fatigue is considered as a risk factor for developing playing-related muscular disorders among professional pianists and could affect musical performance. This study investigated in 50 pianists the effect of fatiguing repetitive piano sequences on the development of forearm muscle fatigue and on piano performance parameters. Results showed signs of myoelectric manifestation of fatigue in the 42-electromyographic bipolar electrodes positioned on the forearm to record finger and wrist flexor and extensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 77 publications
(38 reference statements)
1
36
1
Order By: Relevance
“…The potential of grids of electrodes in revealing spatial inhomogeneities in muscle excitation has, indeed, been recently explored in piano players. In contrast with our results, Goubault et al [ 18 ] reported a significantly greater decrease of the median frequency of EMGs detected from extensor rather than flexor, forearm muscles in professional piano player when performing classical excerpts. Giving we observed more frequent excitation of flexor muscles across subjects when playing classical excerpts, reasonably, one could expect fatigue to be more likely to manifest in flexor than extensor muscles.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The potential of grids of electrodes in revealing spatial inhomogeneities in muscle excitation has, indeed, been recently explored in piano players. In contrast with our results, Goubault et al [ 18 ] reported a significantly greater decrease of the median frequency of EMGs detected from extensor rather than flexor, forearm muscles in professional piano player when performing classical excerpts. Giving we observed more frequent excitation of flexor muscles across subjects when playing classical excerpts, reasonably, one could expect fatigue to be more likely to manifest in flexor than extensor muscles.…”
Section: Discussioncontrasting
confidence: 99%
“…A possible explanation for this disconnect between studies is the load sharing between and within muscles. In the study of Goubault et al [ 18 ], subjects played for a substantially longer time than our subjects did. During the relatively short playing time considered here, spatial inconsistencies in the excitation of extensor muscles across subjects could have been due to the redistribution of excitation among different extensor muscles, a mechanism sought to delay fatigue [ 32 ].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…While participants used one of their fingers to perform key hits, muscles such as the extensor digitorum were used to release the finger from the button. The extensor digitorum superficialis is more susceptible to muscle fatigue than the flexor digitorum superficialis in typing work 28 ) , and piano key hits with similar movements are associated with signs of fatigue in the extensor rather than in the flexor 14 ) . Considering that the load on the extensor muscles was high for key hits, we decided to implement static stretching for the extensor muscles of the forearm.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Therefore, these injuries may have long-term negative consequences that decrease an athlete’s performance 13 ) . During piano performance, which exhibits similarities to the keystrokes used by gamers, muscle fatigue is considered a risk factor for developing muscle-related muscular disorders and decreased performance ability 14 ) . The body gets stressed under such conditions and requires daily care.…”
Section: Introductionmentioning
confidence: 99%